Mechanical properties, corrosion resistance, and osteogenic potential of biodegradable Mg–Zn–Mn–Ca alloys - Wenyue Yang; Xiaomin Chen; Hao Gu; Li Li; Jiaying Gu; Yuan Zhang; Xiaoyu Gu; Chenyuan Zhu; Miao Luo; Liqiang Wang; Changxi Liu; Yuanfei Fu (Journal of Materials Research and Technology)
Biodegradable magnesium (Mg)-based materials show promise for orthopedic implants but continue to face challenges such as limited mechanical strength, rapid corrosion, and insufficient osteogenic performance. Alloying offers a practical solution by improving these properties and mitigating their rapid degradation in physiological environments. In this study, we designed novel Mg–Zn–Mn–Ca alloys with 2 wt% and 3 wt% Zn (referred to as Mg2Zn and Mg3Zn), harnessing the synergistic effects of Zn, Mn, and Ca to enhance mechanical properties, corrosion resistance, and biological performance. Both alloys outperformed pure Mg in mechanical tests; notably, Mg3Zn achieved an ultimate tensile strength of 206.5 MPa and an elongation of 30.1 %, underscoring a balance of strength and ductility. Corrosion analysis showed that Mg3Zn had the lowest corrosion rate (1.17 mm/year) and formed compact, insoluble corrosion products. Regarding osteogenic potential, Mg2Zn enhanced Runx2 expression 1.69-fold, while Mg3Zn increased Ocn expression 1.95-fold relative to the control, with Mg3Zn consistently showing higher osteogenic capacity. Altogether, Mg–Zn–Mn–Ca alloys demonstrated enhanced mechanical properties and excellent osteogenic potential, with the 3 wt% Zn alloy providing superior corrosion resistance and mid-to-late-stage osteogenesis. These findings position Mg3Zn as a strong candidate for biodegradable metallic orthopedic implants with significant clinical potential.